Marketing digital y el posicionamiento del Restaurante Ginger Café en la ciudad de Babahoyo - Vargas Arboleda, Jairon Luis (2023)
This degree project focuses on Ginger Café, a restaurant located in Babahoyo, Los Ríos province, specialized in offering food and beverages for onsite consumption, including breakfasts, barbecues and typical Ecuadorian dishes. The lack of promotion and definition of the target audience hinders its positioning in the market and limits the connection with customers. To address this challenge, the strategic and content marketing approach was used, supported by an exhaustive research of bibliographic sources, previous studies and terms related to the field. The methodology encompassed the deductive and inductive approach, resulting in a mixed approach with a descriptive/exploratory scope. To collect data, surveys, interviews and observation sheets were conducted in order to understand consumer preferences and the factors that influence purchasing decisions. This methodology allowed for an in-depth analysis of the restaurant's dynamics and its interactions with customers.............